The Viability of Indigenous Rhizosphere Fungi of Kirinyuh (Chromolaena odorata) as a Biofungicide for Controlling Anthracnose in Red Chili (Capsicum annuum L.) - Aji, Aji; Sidiq, Roni Maulana; Agustin, Gina Sonia; Sari, Serly Marsita; Hamdayani, Annisa; Benatar, Gilang Vaza (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Anthracnose disease caused by Colletotrichum spp. has reduced red chili production in Indonesia, thus requiring control measures that can suppress anthracnose in a more environmentally friendly manner. This research aims to explore the potential of rhizosphere fungi from kirinyuh as a biological agent in controlling anthracnose disease in red chili peppers. (Capsicum annuum L.). Isolates found in the rhizosphere of kirinyuh were identified and then tested for hypersensitivity, in vitro, and in vivo. Eleven rhizosphere fungal isolates from kirinyuh were suspected to belong to the genera Penicillium, Blastomyces, Sepedonium, Aspergillus, Tricladium, and Rhizoctonia, and did not show pathogenicity traits on plants based on hypersensitivity tests. The results of in vitro tests show that the isolate with code CRKF can suppress the growth of Colletotrichum by up to 46%. Meanwhile, in in vivo tests, the CRKA isolate (Penicillium) was able to reduce the intensity of attacks by 13%, the CRKH isolate effectively reduced fruit shrinkage, and the CRKI isolate was proven to slow down the incubation period by up to 4 HSI.